2020
DOI: 10.1002/hed.26376
|View full text |Cite
|
Sign up to set email alerts
|

Prelacrimal approach vs conventional surgery for inverted papilloma in the maxillary sinus

Abstract: Background: The prelacrimal approach, termed endoscopic modified medial maxillectomy (EMMM), has recently been applied for treatment of inverted papilloma (IP) in the maxillary sinus. EMMM provides wider access to the maxillary sinus while preserving the inferior turbinate and nasolacrimal duct. Methods: We reviewed patients with IP in the maxillary sinus to compare the surgical results obtained by conventional surgery (ie, endoscopic maxillary sinus antrostomy or in combination with the Caldwell-Luc approach)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Moreover, surgical morbidity after resection of inverted papillomas using the EPLRA was low in previous reports. 1,7,13,22 . Persistent nasal crusting and epiphora were not observed in the studies included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surgical morbidity after resection of inverted papillomas using the EPLRA was low in previous reports. 1,7,13,22 . Persistent nasal crusting and epiphora were not observed in the studies included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the PLWA was compared to conventional methods (traditional endoscopic, open and combined) with regard to treatment results of surgically resected inverted papillomas within the maxillary sinus. No recurrence was found in the PLWA group, while conventional methods yielded a 16% recurrence rate 13 . Tran et al 14 reported a case series of surgically treated maxillary sinus hemangiomas via PLWA.…”
Section: Discussionmentioning
confidence: 77%
“…A recent study compared the PLWA against conventional approaches (traditional endoscopic, open and combined) in treatment outcomes of surgically resected inverted papilloma (IP) within the maxillary sinus. The authors found no recurrences in the PLWA group whereas conventional surgery resulted in a 16% recurrence rate -all located in the alveolar recess (4) . Hildenbrand et al (5) evaluated the long-term outcome of maxillary sinus IP, treated via PLWA, and observed no recurrences after a median follow-up period of 3.8 years.…”
Section: To the Editormentioning
confidence: 89%
“…Hildenbrand et al (5) evaluated the long-term outcome of maxillary sinus IP, treated via PLWA, and observed no recurrences after a median follow-up period of 3.8 years. A series of studies have concluded that the PLWA is a safe and effective endoscopic treatment of various diseases within the maxillary sinus, including benign and malignant pathologies (4)(5)(6)(7)(8) .…”
Section: To the Editormentioning
confidence: 99%